2018
DOI: 10.1186/s13063-018-2812-3
|View full text |Cite
|
Sign up to set email alerts
|

Arsenic trioxide and all-trans retinoic acid (ATRA) treatment for acute promyelocytic leukemia in all risk groups: study protocol for a randomized controlled trial

Abstract: BackgroundThe treatment of acute promyelocytic leukemia (APL) has been revolutionized in the past two decades by the advent of all-trans retinoic acid (ATRA) and arsenic trioxide (ATO). It suggests that non-high-risk APL patients can be cured without chemotherapy. However, ATRA plus chemotherapy is still the standard therapy for the high-risk patients. Central nervous system (CNS) relapse remains a significant cause of treatment failure in high-risk patients. However, increasing the ATO concentration in cerebr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(36 citation statements)
references
References 17 publications
0
36
0
Order By: Relevance
“…We started a trial about the simultaneous application of ATRA and ATO in post-remission therapy. It was registered with the Chinese Clinical Trial Registry (ChiCTR-IPR-15006821) (24). To date, none of the participants relapsed.…”
Section: Discussionmentioning
confidence: 99%
“…We started a trial about the simultaneous application of ATRA and ATO in post-remission therapy. It was registered with the Chinese Clinical Trial Registry (ChiCTR-IPR-15006821) (24). To date, none of the participants relapsed.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to chemotherapy alone, ATRA resulted in significantly higher remission rates in APL patients [28] but even projected more promising outlooks when combined with a standard dose of induction chemotherapy. [29,30] Likewise, combined treatment of APL cells with ATRA and arsenic trioxide (ATO), a small molecule with known anti-leukemic properties, resulted in longlasting terminal differentiation and sustained demethylation of target genes suggesting a relapse-free treatment strategy. [30,31] The promising results observed in patients with advanced APL were a major driving force for testing ATRA on solid tumors.…”
Section: Retinoic Acid-mediated Signaling Pathwaysmentioning
confidence: 99%
“…[29,30] Likewise, combined treatment of APL cells with ATRA and arsenic trioxide (ATO), a small molecule with known anti-leukemic properties, resulted in longlasting terminal differentiation and sustained demethylation of target genes suggesting a relapse-free treatment strategy. [30,31] The promising results observed in patients with advanced APL were a major driving force for testing ATRA on solid tumors. Biological models have previously demonstrated that ATRA is equally capable of enforcing apoptosis and/or differentiation via the RA receptor pathway in other organs.…”
Section: Retinoic Acid-mediated Signaling Pathwaysmentioning
confidence: 99%
“…This study showed that ATO can replace chemotherapy in high-risk patients, without increasing the risk of relapse and with a milder toxicity profile in terms of myelosuppression and infectious episodes. The randomized, multicenter, pan-European APOLLO trial (NCT02688140) and a Chinese study [45] are ongoing to specifically assess the role of ATO/ ATRA frontline in high-risk APL.…”
Section: Clinical Use Of Arsenic In Apl: the Long Journey To A Chemotmentioning
confidence: 99%